Early Characteristics and Progression of Blunt Traumatic Aortic Injuries at a Single Level I Trauma Center. (February 2021) - Cheng, Daniel; McNickle, Allison G.; Fraser, Douglas R.; Carroll, Joseph T.; Vega, Jorge A.; Dickhudt, Timothy; Bombard, Judzia; Kuhls, Deborah A.; Chestovich, Paul J.
Objectives: The most widely accepted grading system for blunt traumatic aortic injury (BTAI) by the Society of Vascular Surgery (SVS) recommends endovascular repair for grade 2 and greater. Non-operative management in grade 2 injuries has been shown to be reasonable in certain circumstances. The natural history of low-grade injuries (1, 2) when managed non-operatively is not well defined. Methods: Utilizing our trauma registry, patients from 2013 to 2016 with blunt traumatic injury who underwent initial computed tomography were identified. Aortic pathology was graded and grouped by SVS classification. Clinical courses were reviewed for timing of interventions, repeat imaging, concurrent injuries, and outcomes. Analysis of variance and Chi-square tests of significance were utilized to compare between groups. Results: Out of 10, 178 patients, we identified 32 with BTAI (grade: 1 (n = 13), 2 (n = 5), 3 (n = 3), 4 (n = 11)). High-grade injuries (3, 4) resulted only from motor vehicle, motorcycle, and pedestrian mechanisms. Initially, 9 patients (28%) required intervention, 5 (16%) were treated non-operatively, and 18 (56%) underwent repeat imaging. On repeat imaging, injuries that did not resolve remained stable and no injuries were found to progress. Of these patients, 9 (50%) required delayed intervention and 9 (50%) successfully underwent non-operative management. Patients with low-grade injuries were more likely to have successful non-operative management than those with high-grade injuries (72% vs 7%; p < 0.01). Conclusions: While low-grade injuries generally have good outcomes, some ultimately do require delayed intervention, and short-term imaging is not reliable in identifying these cases.